Efficacy of PD‐1/PD‐L1 inhibitors in patients with non‐small cell lung cancer and brain metastases: A real‐world retrospective study in China - Jiamin Sheng (Wiley, 2021)
Abstract Background There is only limited knowledge of the treatment responses and clinical outcomes of immune checkpoint inhibitors (ICIs) in driver gene‐negative non‐small cell lung cancer (NSCLC) patients with brain metastases (BM). This study aims to assess the efficacy of immunotherapy in these patients in a real world setting. Methods NSCLC‐BM patients without driver gene mutations who received ICIs were retrospectively identified between July 2017 and December 2019. The primary observation endpoint was intracranial objective response rate (iORR), and secondary objectives were objective response rate (ORR), intracranial and systemic progression‐free survival (iPFS, PFS), and overall survival (OS). Results We reviewed 1578 patients with lung cancer and BM. According to the exclusion criteria, 41 patients were finally enrolled. Among these 41 patients, iORR was 36.6% (95% confidence interval [CI] = 21.2%–52.0%), whereas iPFS was 6.8 (95% CI = 3.32–10.35) months. Additionally, ORR, PFS, and OS were 24.4% (95% CI = 10.7%–38.1%), 6.2 (95% CI = 4.57–7.83) months and 13.7 (95% CI = 11.20–16.26) months, respectively. ICIs combined with concurrent radiotherapy group exhibited preferred iORR (p = 0.030) compared with no radiotherapy group, and ICIs plus chemotherapy showed improved OS (p = 0.024) compared to ICI monotherapy. Moreover, the lines of ICI treatment ≥2 (p = 0.005) and derived neutrophil‐to‐lymphocyte ratio (dNLR) ≥3 (p = 0.010) were independently negative factors for OS. Conclusion In NSCLC‐BMs patients lacking driver genes, ICIs exhibited an effective drug regime. A combination of ICIs with concurrent radiotherapy showed a better intracranial response, whereas ICIs plus chemotherapy were associated with superior OS.